Keterlibatan Pemuda Dalam Pembangunan Desa Partibi Lama Kecamatan Merek - Darinda Sofia Tanjung; Arisan Laia; Dina Sitohang; Dearin Jely Sinaga; Madonna Irene Situmorang (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
Youth involvement in the development of Partibi Lama Village, Brand District, which has high potential but is faced with the challenge of minimal community participation. The research objective is to facilitate youth participation in development through an inclusive model and analyze the effectiveness of the Participatory Action Research (PAR) method. The methods used included in-depth interviews, participant observation, and focus group discussions with 50 young people as a sample. The results show that youth involvement contributes positively to village progress, improving social relations and innovation. The implications of this research encourage the development of training programs and the creation of participatory spaces for youth in village decision making.